Measurement error in minimum wage evaluations using survey data - Mario Bossler; Christian Westermeier (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2020)
We assess the role of measurement error in minimum wage evaluations when the treatment variable - the bite - is inferred from a survey wage distribution. We conduct Monte Carlo experiments on both simulated and empirical distributions of measurement error derived from a record linkage of survey wages and administrative data. On the individual-level treatment effects are downward biased by more than 30 percent. Aggregation of the treatment information at the household, firm or region level does not fully alleviate the bias. In fact, the magnitude and direction of the bias depend on the size of the aggregation units and the allocation of treated individuals to such units. In cases of a strongly segregated allocation, measurement error can cause upward biased treatment effects. Besides aggregation, we discuss two possible remedies: the use of a continuous treatment variable and dropping observations close to the minimum wage threshold. – – Wir analysieren den Einfluss von Messfehlern in Mindestlohnevaluationen, wenn die Treatmentvariable, also der 'Bite', aus einer befragungsbasierten Lohnverteilung stammt. In Monte-Carlo-Simulationen überprüfen wir die Verzerrtheit der Schätzer sowohl mit simulierten als auch empirischen Verteilungen von Messfehlern. Die empirischen Messfehler stammen aus einem Link von Befragungsdaten und administrativen Daten. Auf der individuellen Beobachtungsebene werden die Treatmenteffekte über 30 Prozent unterschätzt. Eine Aggregation der Treatmentinformation auf der Ebene von Haushalten, Firmen oder Regionen löst das Problem nicht vollständig. In Fällen einer sehr stark segregierten Verteilung von betroffenen Beschäftigten auf nur wenige Firmen oder Regionen kann es sogar zu einer Überschätzung des wahren Effekts kommen. Wir diskutieren zwei Lösungsansätze: Die Verwendung einer kontinuierlichen Treatmentvariable und das Löschen von Observationen, die in der Lohnverteilung nahe der Mindestlohnschwelle liegen.
Keywords: C21; C43; J38; 330; attenuation bias; difference-in-differences; measurement error; minimum wage; misclassification; record linkage; treatment effects; survey data; wage distribution